Effects of intermediate and long-term exposure to ambient air pollution and temperature on hospital admissions with second cardiovascular events among medicare beneficiaries - Mahdieh Danesh Yazdi; Yaguang Wei; Qian Di; Weeberb J. Requia; Adjani A. Peralta; Francesca Dominici; Joel D. Schwartz (Environment International)
Background: Air pollution has been linked to cardiovascular diseases (CVDs). In this study, we assess whether exposure to air pollutants and ambient temperature is associated with repeated admissions with adverse cardiovascular outcomes. Methods: We used data from Medicare beneficiaries between 2000 and 2016 to look at the effects of intermediate and long-term exposure to ambient PM2.5, NO2, O3, and temperature on second admissions with myocardial infarction (MI) and ischemic stroke. We derived exposure levels from high-resolution spatiotemporal models. We adjusted for demographic, socioeconomic, and access-to-care characteristics. Cox proportional hazards models were used to assess these relationships. We further looked at the effects of exposure at lower air pollution concentrations defined as PM2.5 < 9 µg/m3, NO2 < 25 ppb, and O3 < 50 ppb. Results: PM2.5 and NO2 increased the hazard of second admissions with both MI and stroke. For PM2.5, the effects were more pronounced for longer exposure time windows. Each µg/m3 increase in one-year PM2.5 levels before the first admission increased the hazard of a second admission with MI by 1.1% (95% CI: 1.0%-1.2%) and stroke by 0.9% (95% CI: 0.8%-1.1%). O3 exhibited a slight protective effect for both outcomes. Higher temperatures were associated with a higher hazard of second admissions with stroke. These results persisted at lower concentrations. Conclusion: Our study demonstrates that exposures to PM2.5 and NO2 are associated with increased rates of second admissions with MIs and strokes. Higher temperatures were also further associated with an increase in the rate of second admissions with stroke.